Towards Metacognition, Autonomy, and Learners’ Knowledge/Meaning Construction in EFL Context - ZHIRI, Younes (International Journal of English Literature and Social Sciences (IJELS), 2019)
The teaching-learning enterprises at the tertiary level in Morocco have been at stake since the 2003 educational reform. A decrease in quality and academic achievement has been noticed since then in all disciplines. English departments are no exception of this flaw. Putting a number of political and social factors aside, this paper addresses the problem from the perspective of the teacher-learner who remained traditional in a multi-faceted changing world of globalization and technology. Over the years, the teacher-student relationship has resisted change and remained verticalin the sense that most of the teaching has always taken the form of teacher lecturing and students listening. Additionally, faculty, due to one reason or another, care only about the teaching of content. Less effort, in this respect,has been devoted to coaching/training students to exercise a degree of autonomy. The majority of learners do not even make sense of the information they receive. The result, students do poorly in exams and teachers get a negative feedback about what they teach. Thus, this paper shows that engaging students in the construction of meaning by training them on self-directed learning and metacognition can yield positive learning outcomes. To make our claims credible, this paper uses the results of an experiment conducted about the learning of tense and aspect by English department Semester 1 Moroccan university students at the faculty of Arts and Humanities- IbnTofail University during the academic year 2012-2013.